PENGEMBANGAN SISTEM IRIGASI TETES DENGAN GRAVITASI SISTEM KONTROL OTOMATIS MENGGUNAKAN LIPSTIK - Nurjumadil, Muhammad; Hermawati, Hermawati; Adil, Adil; Mustarin, Amira (Jurnal Pendidikan Teknologi Pertanian, 2018)
Agriculture is generally defined as a cycle of management or cultivation of natural resources by humans, especially in the field of crop resources management. The cultivation process requires several supporting factors to run normally and well, the better the process of agricultural cultivation will be the maximum and the quality of the products produced, and vice versa. Factors determining whether or not the quality of the plant, is determined by 2 main factors, namely land or planting media and the maintenance process because the planting medium is where the growth of plants consisting of solid, liquid and air and the bodies of different content for each type of soil, In order for plant growth can take place properly then the regulator of water antata must be considered, because water directly affect the preparation of plant body and photosynthesis process. One of the most important factors in improving the quality of plants is at the pre-harvest stage, ie there is a watering stage. In the process of watering there is to be considered that the pattern or time of watering because it has a correlation to the process of photosynthesis, especially on horticultural crops are generally in demand by the community as food crops. Based on the main points of mind on the main problem that is, urban communities in the care of plants do not have much time in due to the density of human activity, in the care of the plants is very urgent attention to watering, plant watering done by farmers or urban communities today is generally still done traditional by using timbah or hose directly to water the plants, so in this way is still less efficient because it still rely on human power and not time saving, and the high level of heterogeneity in the distribution of water, then on the other hand many available plastic waste such as plastic cups, paint containers and other plastic containers. So the researchers make innovations and the need for the development of irrigation watering equipment drops with the gravity of automatic control system using plastic waste (LIPSTIK)